2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid compensatory changes in GABA receptor efficacy in rat vestibular neurones after unilateral labyrinthectomy

Abstract: 1. The inhibitory effects of the GABAA agonist muscimol and the GABAB agonist baclofen on tonically active medial vestibular nucleus (MVN) neurones were recorded in slices of the rat dorsal brainstem in vitro, to determine whether any changes occurred in the functional efficacy of GABAergic inhibition in these cells during the initial rapid stage of 'vestibular compensation', the behavioural recovery that takes place after unilateral labyrinthectomy (UL). These experiments were carried out in preparations wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 37 publications
(42 reference statements)
9
98
1
Order By: Relevance
“…In particular, we have observed that the proportions of type A and B MVNn were varying along the rostrocaudal extent of the nucleus (N. Vibert, M. Serafin, M. Mühle-thaler, unpublished data). Other authors have demonstrated that the cellular changes associated with vestibular compensation can be different in the caudal and rostral parts of the MVN (Cameron and Dutia 1997;Yamanaka et al 2000). To control for this variability, we decided to restrict as much as possible our recordings to the two 500-m coronal slices corresponding to the middle third of the guinea pig MVN, at the level of the cerebellar peduncles.…”
Section: Intracellular Electrophysiological Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we have observed that the proportions of type A and B MVNn were varying along the rostrocaudal extent of the nucleus (N. Vibert, M. Serafin, M. Mühle-thaler, unpublished data). Other authors have demonstrated that the cellular changes associated with vestibular compensation can be different in the caudal and rostral parts of the MVN (Cameron and Dutia 1997;Yamanaka et al 2000). To control for this variability, we decided to restrict as much as possible our recordings to the two 500-m coronal slices corresponding to the middle third of the guinea pig MVN, at the level of the cerebellar peduncles.…”
Section: Intracellular Electrophysiological Recordingsmentioning
confidence: 99%
“…Vestibular compensation involves modification of both the intrinsic properties of the ipsilesional MVNn and the vestibular-related networks in which they are embedded (Cameron and Dutia 1997;Darlington and Smith 1996;Darlington et al 2002;Vibert et al 1999aVibert et al , 2000Yamanaka et al 2000). We recently suggested that in rodents, the spontaneous discharge recovered in vivo by the ipsilesional MVNn might be more and more sustained by changes in the intrinsic properties of MVNn themselves as the time of compensation increases (Vibert et al 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that heat shock induced a statistically significant increase in the expression of UNC-49 protein in worms exposed to thermal stress in relation to the non-exposed group. The effect was more apparent in body muscle cells than in head muscle cells and could be a result of a compensatory response to oxidative damage on UNC-49 as reported in other models (Fritschy et al 1999;Yamanaka et al 2000;Zeller et al 2008).…”
Section: Discussionmentioning
confidence: 53%
“…Although it is uncontested that the four major neurotransmitters, GABA, glycine, glutamate, and acetylcholine, are involved in the process of neuroplastic changes in VC, a clear picture has not yet emerged, probably because of differences within species. In rats, for example, Yamanaka [34] reported a compensatory down-regulation of inhibitory GABA-A and GABA-B receptors ipsilesional and an upregulation of GABA-B receptors contralesional. Changes in GABA receptor efficacy, thus, could be interpreted in the context of reducing the imbalance between the bilateral MVN [20,34,35].…”
Section: Biochemical Mechanisms Of Recoverymentioning
confidence: 99%
“…In rats, for example, Yamanaka [34] reported a compensatory down-regulation of inhibitory GABA-A and GABA-B receptors ipsilesional and an upregulation of GABA-B receptors contralesional. Changes in GABA receptor efficacy, thus, could be interpreted in the context of reducing the imbalance between the bilateral MVN [20,34,35]. No such changes, however, were found in mice within one week after UVD, while still in mice instead an increase of glutamate receptor activation in the MVN was observed as early as within 4 hours after UVD [36].…”
Section: Biochemical Mechanisms Of Recoverymentioning
confidence: 99%